Combination therapy with normobaric oxygen (NBO) plus thrombolysis in experimental ischemic stroke - Singhal Aneesh B (BMC Neuroscience, 2009)
Abstract Background The widespread use of tissue plasminogen activator (tPA), the only FDA-approved acute stroke treatment, remains limited by its narrow therapeutic time window and related risks of brain hemorrhage. Normobaric oxygen therapy (NBO) may be a useful physiological strategy that slows down the process of cerebral infarction, thus potentially allowing for delayed or more effective thrombolysis. In this study we investigated the effects of NBO started simultaneously with intravenous tPA, in spontaneously hypertensive rats subjected to embolic middle cerebral artery (MCA) stroke. After homologous clot injection, animals were randomized into different treatment groups: saline injected at 1 hour; tPA at 1 hour; saline at 1 hour plus NBO; tPA at 1 hour plus NBO. NBO was maintained for 3 hours. Infarct volume, brain swelling and hemorrhagic transformation were quantified at 24 hours. Outcome assessments were blinded to therapy. Results Upon clot injection, cerebral perfusion in the MCA territory dropped below 20% of pre-ischemic baselines. Both tPA-treated groups showed effective thrombolysis (perfusion restored to nearly 100%) and smaller infarct volumes (379 ± 57 mm3 saline controls; 309 ± 58 mm3 NBO; 201 ± 78 mm3 tPA; 138 ± 30 mm3 tPA plus NBO), showing that tPA-induced reperfusion salvages ischemic tissue and that NBO does not significantly alter this neuroprotective effect. NBO had no significant effect on hemorrhagic conversion, brain swelling, or mortality. Conclusion NBO can be safely co-administered with tPA. The efficacy of tPA thrombolysis is not affected and there is no induction of brain hemorrhage or edema. These experimental results require clinical confirmation.